Wave Impact on a Vertical Baffle - Nor Aida Zuraimi, Md Noar; Greenhow, Martin (2015)

(untitled)
A fluid-structure interaction phenomenon is an important consideration in several engineering fields. When a tank truck is braking, turning or in collision, the liquid in the partially-filled tank will slosh or even splash due to the oscillating of the unrestrained free surface of the liquid. The study of the pressure impulse on the baffles and walls can provide data on the impacts acting on the tank and baffles which can be used for simulating handling stability, especially for planes, rockets and spacecraft. We consider the wave impact against a vertical baffle in four cases: (i) A vertical baffle at free surface; (ii) A vertical baffle in front of a wall; (iii) A vertical baffle at a deck in front of a seawall; (iv) A vertical baffle on the seabed in front of a wall. The mathematical formulation and the boundary conditions for four cases of baffles which have different positions are presented using the pressure impulse theory. We used a basis function method to solve the mathematical formulation, and total impulse and moment impulse are investigated for each problem. The influence of the depth of baffle penetration and the size of the impact region is also studied. We can see different of impact pressure impulse for different case of baffle. We note that pressure impulse on the baffles almost same for case (i),( ii) and (iii) for different length of baffles with same size of impact. However the pressure impulse behind the baffles decreases when the length of baffle increases for case (ii) and (iii). For case (iv), the pressure impulse on the wall and behind the baffles increases when the length of baffle on the seabed increases